The Effect of Implementing Total Quality Management (TQM) on the Performance of Employees: A Field Study on Private Service Organizations in Amman - Shammout, Ahmad Bahjat; Jawazneh, Ahmad Khaled (Jordan Journal of Business Administration, 2022)
This study aimed to investigate the impact of total quality management (including top management support, continuous improvement, employee involvement, employee training and incentives and rewards) on employees’ performance in private service organizations in Amman. The degree to which each of these dimensions has an impact on employees’ performance was also the focus of this study. Based on a convenience sample of 469 employees in the private service sector in Amman, the results of this study revealed that -with the exception of top management support and continuous improvement dimensions- it was found that employee involvement, employee training and incentives and rewards have a positive effect on employees’ performance. Interestingly, employee training was found the highest among total quality management dimensions affecting employees’ performance, followed by incentives and rewards and employee involvement, respectively. The findings suggest the need for managers in the service sector to implement strategies that enhance their support and continuous improvement as key factors of total quality management practice. Furthermore, they are required to maintain a superior rewarding system for employees, continue encouraging employees’ participation and keep providing proper training programs.